Exploring precalculus with the Geometer's sketchpad - Scher, Daniel; Key Curriculum Press (Emeryville, CA : Key Curriculum Press, 2005)
Allows students to directly experience, through dynamic visualization and manipulation, the topics covered in precalculus.
Function transformations -- Circular functions -- Trigonometric properties -- Other functions -- Data and probability -- Vectors and matrices -- Polar coordinates and complex numbers -- Sequence and series -- Introduction to calculus.
System requirements for accompanying CD-ROM: Windows or Macintosh; CD-ROM drive; Geometer's Sketchpad version 4.0 or later.
Keywords: Geometer's Sketchpad; Algebra -- Study and teaching (Higher); Algebra -- Study and teaching (Secondary); Functions -- Study and teaching (Secondary)